“Human Desire” y “La Bête humaine”: una relación compleja - Fernando Gonzáles Garcia (Prof. Rinaldo Rinaldi, 2021)
The path that moves from Émile Zola’s novel “La Bête humaine” to the homonymous film by Jean Renoir (1938), then to the remake “Human Desire” (1954) by Fritz Lang, conveyed a complex series of elements linked to European and American publishing and film industries. This transnational perspective brings into play an 'intermedial' circle, which this article attempts to describe in detail.